African countries and the World Trade Organisation dispute settlement mechanism : underlying constraints, concerns and proposals for reform - Muheki, Stella (University of Pretoria, 2013)
At the inception of the World trade organization (WTO) in 1995, the organization's provisions for a formal dispute settlement mechanism under the Understanding on Rules and Procedures Governing the Settlement of Disputes (DSU) stood out as state of the “art”, “crown” and “jewels” of the WTO. Fifteen years later on, an assessment of the Dispute Settlement Body (DSB)’s judicial records shows that the system has indeed reduced the role of international diplomacy, while strengthening the rule of law in dispute settlement. The WTO-DSU’s independent Appellate Body, strict deadlines within which to settle disputes and binding panel recommendations certainly supersede the 1947 General Agreement on Tariffs and Trade (GATT) dispute settlement system. To date, 400 disputes have been lodged before the Dispute Settlement Body leading to establishment of over 140 panels and adoption of 218 panel/Appellate Body reports. However, what these statistics fail to show is the fact that the DSM is dominated by leading industrialized countries, notably the European Communities and the United States, at the expense of developing countries. The European communities and the United States in particular are said to be employing the DSU to achieve their aspirations in international trade. This arises from their retaliatory capacity to threaten weaker respondents from pursuing disputes against them among other reasons. It follows that despite of the uniqueness and widely recognized efficacy, the WTO Dispute Settlement Mechanism has largely failed to address the needs of developing/ least developed countries, especially in Africa. The system’s lack of meaningful remedies, lack of transparency and general insensitivity to the development concerns of African countries have worked to alienate African states from the dispute settlement process. The said shortcomings in the pattern and structure of the DSU have also been noted from all corners of WTO membership including the original architects of the System like India, Brazil and Australia. In light of the above, this research paper analyzes the process of dispute settlement at the WTO, with special emphasis on the nature of remedies available to parties under the DSU. The research identifies pertinent areas for reform in the DSU and the DSB as a whole. The research arrives at practical measures/alternatives that African countries could adopt in order to enhance participation in dispute settlement at the WTO. The research points out that WTO law is tailored through interpretation of covered agreements and precedents and that participation in the WTO dispute settlement system is therefore crucial to the shaping of WTO law in the long run. In the end, African countries (forming a large percentage of WTO Membership) have not made use of the dispute settlement mechanism despite their trade being affected by the protectionist trade policies of their developed counterparts. If the majority of WTO membership cannot access the DSM, then the WTO objective of enhancing security and predictability of the multilateral trading system remains fictitious. This research therefore adds to the voice of many that the amendment of the DSU is long overdue. === Dissertation (LLM)--University of Pretoria, 2010. === Centre for Human Rights === unrestricted